CENPE, PRC1, TTK, and PLK4 May Play Crucial Roles in the Osteosarcoma Progression. (11th November 2020) - Wang, Fei; Zhao, Qiheng; Liu, Wenping; Kong, Daliang
Osteosarcoma (OS) is a cancerous tumor in a bone. We aimed to identify the critical genes involved in OS progression, and then try to elucidate the molecular mechanisms of this disease. The microarray data of GSE32395 was used for the present study. We analyzed differentially expressed genes (DEGs) in OS cells compared with control group by Student's t-test. The significant enriched gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) pathways were analyzed for upregulated genes and downregulated genes, respectively. In addition, a protein-protein interaction (PPI) network was constructed. GO and KEGG enrichment analyses were conducted for genes in the PPI network. In total, 183 DEGs, including 100 upregulated DEGs and 83 downregulated DEGs were screened. The upregulated DEGs were significantly enriched in 2 KEGG pathways, such as "Glycosaminoglycan biosynthesis-chondroitin sulfate" and the downregulated DEGs were significantly enriched in 12 pathways, including "cell adhesion molecules, " "pentose phosphate pathway" and "allograft rejection." GO enrichment analysis indicated that the upregulated DEGs were significantly involved in biological process, such as "multicellular organismal metabolic process" and "limb morphogenesis, " while the downregulated DEGs were significantly enriched in biological process, such as "Positive regulation of pathway-restricted SMAD protein phosphorylation." The PPI network included 84 interactions and 51 nodes. The "glycosaminoglycan biosynthesis-chondroitin sulfate pathway, " "microtubule motor activityfunction, " and "regulation of mitosis process" were significantly enriched by genes in PPI network. In particular, CENPE, PRC1, TTK, and PLK4 had higher degrees in the PPI network. The interactions between TTK and PLK4 as well as CENPE and PRC1 may involve in the OS development. These 4 genes might be possible biomarkers for the treatment and diagnosis of OS.